2008
DOI: 10.1086/591501
|View full text |Cite
|
Sign up to set email alerts
|

Mice That Overexpress CC Chemokine Ligand 2 in Their Lungs Show Increased Protective Immunity to Infection withMycobacterium bovisBacille Calmette‐Guérin

Abstract: The data of the current study suggest that CCL2-dependent amplification of endogenous host-defense programs in the lung may improve the lungs' protective immunity against mycobacterial infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
19
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…Previous reports demonstrated that CCL2 was upregulated during infectious (42) and noninfectious lung injury (5,10,41,52). CCL2 has been showed to induce leukocyte infiltration during inflammation (8,38,39,43). Overexpression of human CCL2 in alveolar type II epithelial cells elicited a substantial recruitment of monocytic cells into both parenchymal and alveolar compartments of mouse lungs in the absence of lung inflammation (19).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous reports demonstrated that CCL2 was upregulated during infectious (42) and noninfectious lung injury (5,10,41,52). CCL2 has been showed to induce leukocyte infiltration during inflammation (8,38,39,43). Overexpression of human CCL2 in alveolar type II epithelial cells elicited a substantial recruitment of monocytic cells into both parenchymal and alveolar compartments of mouse lungs in the absence of lung inflammation (19).…”
Section: Discussionmentioning
confidence: 99%
“…inflammation resolution; apoptosis; acute lung injury ACCUMULATION OF LEUKOCYTES at sites of inflammation is essential for host defense during inflammation. CC chemokine ligand-2 (CCL2)/monocyte chemoattractant protein-1 (MCP-1) and its receptor CCR2 have been well documented for their ability to induce leukocyte infiltration during inflammation (8,19,38,39,43). Studies have shown that CCL2 is elevated in various pulmonary diseases, including chronic obstructive pulmonary disease (10), asthma (47), and interstitial lung diseases such as idiopathic pulmonary fibrosis and systemic sclerosis (30,31,44).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…+ mononuclear phagocyte subsets as well as lymphocyte subsets isolated from lung parenchyma and lung dLN were immunophenotypically analyzed according to their cell surface Ag expression profiles, as described previously (24,25). First, the respective CD11c + mononuclear phagocyte subsets purified from lung homogenates of CG/NE-deficient and wild-type mice were gated according to their forward light scatter ( …”
Section: Cd11cmentioning
confidence: 99%